Analysis of Lead (Pb) and Cadmium (Cd) in Oyster Crassostrea gigas and Saccostrea cucullata using Atomic Absorption and Ultraviolet-Visible Spectrophotometer Methods - Lelifajri Lelifajri; Salsabila Salsabila; Khairi Suhud (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2023)
Lead (Pb) and Cadmium (Cd) metals are highly toxic when accumulated in the body and cause serious diseases and even death. This study aimed to determine the metal content of Pb and Cd in the oyster species Crassostrea gigas and Saccostrea cucullate in the Lampulo and Krueng Cut areas at three different places. Analysis of the metals was carried out using AAS and UV-Visible spectrophotometers. Samples were prepared using concentrated HNO3 wet destruction and the addition of dithizone. The results showed Pb measured by AAS in Saccostrea cucullata 2.33-8.00 ppb, and by UV-Vis 2.77-8.66 ppb. Pb within Crassostrea gigas by AAS method 1.77-10.30 ppb, and by UV-Vis method 2.11-10.66 ppb. The Cd metal measured by AAS in Saccostrea cucullate is 3.80-10.50 ppb, and by UV-Vis method is 4.29-10.77 ppb, whereas Cd in Crassostrea gigas measured by AAS is 12.11-13.22 ppb and by UV-Vis method is 12.77-13.66 ppb. Linearity of Pb measurements with AAS and UV-Vis was obtained R2 =0.9979 and R2 =0.9938 and for Cd were R2 =0.9986 and R2 =0.9810. Accuracy (%recorvery) of Pb measurements by AAS and UV-Vis are 80-110% and 98-113% whereas Cd showed 100-106% and 91-107% respectively. The relative value of the standard deviation (%RSD Â± SD) is 0.001 indicating excellent measurement results. Based on t-test calculations, measurements of Pb and Cd levels showed no difference between the AAS method and the UV-Vis method